Possibilities of Improving the Cluster Management System in Increasing the Competitiveness of the Region - Abdikarimova Zilola (Genius Journals, 2023)
Today, competition is the most important factor in all areas of the economy. The level of competitiveness of the region determines the well-being of its population. This article discusses the importance of the cluster management system and foreign experience in increasing the competitiveness of the region.
Keywords: cluster; Iberian model; competitiveness; cluster policy